2017
DOI: 10.5028/jatm.v9i1.726
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Morphological Characteristics of Polyaniline Synthesized in Pilot Scale

Abstract: AbstrAct:Polyanilines have many applications in Aerospace, especially in their doped form. Studies on their synthesis in a pilot scale can contribute to obtain products with desirable characteristics for such applications. The present study reports the chemical oxidative synthesis of polyaniline in pilot scale and different reaction times in order to determine if there are variations in the polyaniline structure, morphology and conductivity due to these synthesis conditions. It is very common to analyze these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 32 publications
(34 reference statements)
3
29
0
Order By: Relevance
“…The signal at 9.4 • may be due to the inter-main chain distance. It was reported that PANI prepared in the presence of sodium dodecylbenzene sulfonic acid (SDBSA) as a surfactant shows no signal at 9.4 • due to a decrease in crystallinity [13]. Similarly, in this study, a decrease in crystallinity compared to the PANI prepared with no surfactant was observed, which was attributed to the presence of scarlet 3R that acted as a surfactant for the synthesis.…”
Section: Xrdsupporting
confidence: 60%
“…The signal at 9.4 • may be due to the inter-main chain distance. It was reported that PANI prepared in the presence of sodium dodecylbenzene sulfonic acid (SDBSA) as a surfactant shows no signal at 9.4 • due to a decrease in crystallinity [13]. Similarly, in this study, a decrease in crystallinity compared to the PANI prepared with no surfactant was observed, which was attributed to the presence of scarlet 3R that acted as a surfactant for the synthesis.…”
Section: Xrdsupporting
confidence: 60%
“…The peak at 323 nm was connected with π-π* excitation, and the peak at 618 nm was connected with the exciton excitation of the quinone rings in the PANI ( Figure 4 a). The presence of these peaks and the dark blue coloration of the solution were characteristic for the emeraldine base [ 23 ]. On the spectrum of the spinning solution containing 1 wt.% of polyacrylonitrile and polyaniline synthesized in DMF, the peak near 320 nm was more visible and shifted in towards the shorter wave ( Figure 4 b).…”
Section: Resultsmentioning
confidence: 99%
“…The reduced state of PAni is related to the conformational changes that occur in the quinoid and benzenoid rings, which are attributed to changes in the 1588 and 1165 cm −1 bands of the oxidized state of PAni, something not shown in Figure 2. In case the PAni is in the protonated state, the Raman spectrum should have a band in the region of 1300 to 1350 cm −1 , which would characterize the quinonic stretch C-N + , which is attributed to the protonated form of the PAni EP, a fact that is not observed in PAni EB film [16][17][18]. With the obtained spectra, it can be stated that the PAni EB present in the binder remains in the oxidized state.…”
Section: Raman Spectroscopymentioning
confidence: 82%
“…Bands in the 1441 cm −1 region are attributed to the presence of OH groups of CEP, and to IEP samples can be associated with C-N bonds of PAni EB binder. The bands at 1603 cm −1 represent the presence of C=C bonds in CEP aromatic rings for the three samples [13,15,18].…”
Section: Raman Spectroscopymentioning
confidence: 99%